2017
DOI: 10.1371/journal.pone.0183944
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of two 4th generation point-of-care assays for the detection of Human Immunodeficiency Virus infection

Abstract: BackgroundFourth generation assays detect simultaneously antibodies for HIV and the p24 antigen, identifying HIV infection earlier than previous generation tests. Previous studies have shown that the Alere Determine HIV-1/2 Combo has lower than anticipated performance in detecting antibodies for HIV and the p24 antigen. Furthermore, there are currently very few studies evaluating the performance of Standard Diagnostics BIOLINE HIV Ag/Ab Combo.ObjectiveTo evaluate the performance of the Alere Determine HIV-1/2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…In fact, the Alere product insert shows that the Alere (p24 Ag component) assay detected 19 of the 28 seroconversion panels earlier than an FDAlicensed anti-HIV-1/2 EIA (31). Another study of serum samples reported sensitivities of the Alere assay of 95% and the SD Bioline assay of 91%; the p24 Ag component of the Alere test detected 10 of 13 acute infection samples (RNA positive, antibody negative), while the SD Bioline assay detected only 1 (32). However, in our study, these assays did not detect samples from the panel at any dilution, indicating either that the Ag component of these assays is not sensitive enough to detect the concentrations tested or that there was inhibition in the assay particular to the preparation of these panels.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the Alere product insert shows that the Alere (p24 Ag component) assay detected 19 of the 28 seroconversion panels earlier than an FDAlicensed anti-HIV-1/2 EIA (31). Another study of serum samples reported sensitivities of the Alere assay of 95% and the SD Bioline assay of 91%; the p24 Ag component of the Alere test detected 10 of 13 acute infection samples (RNA positive, antibody negative), while the SD Bioline assay detected only 1 (32). However, in our study, these assays did not detect samples from the panel at any dilution, indicating either that the Ag component of these assays is not sensitive enough to detect the concentrations tested or that there was inhibition in the assay particular to the preparation of these panels.…”
Section: Discussionmentioning
confidence: 99%
“…All specimens from acutely HIV-1-infected, treatmentnaïve, immunoblot-indeterminate/positive patients (Fiebig stages IV-VI) scored positive in both versions of the Determine™ HIV-1/2 Combo, confirming the high sensitivity of this type of RDT to detect HIV-1 infection in acute infection during or after seroconversion [29][30][31]. Of note, the novel RDT failed to detect HIV-1-specific antibodies Table 3 Detection of chronic HIV-1 infection by the old and new versions of the Alere RDT in plasma specimens from HIV-1-infected patients compared to quantitative PCR, 4G-EIA, and p24 Ag assay…”
Section: Discussionmentioning
confidence: 61%
“…These results indicate an increased sensitivity of the new version of the RDT for detecting early HIV-1 infection prior to seroconversion. Several studies that have recently investigated the performance of the new RDT to detect infection in p24CA-positive, immunoblot-negative serum samples showed lower reactivity rates (< 30%) [30,33], while other groups demonstrated higher reactivity rates of more than 85% in similar specimens [29,31,32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations